2011
DOI: 10.1016/j.neuroimage.2011.02.016
|View full text |Cite
|
Sign up to set email alerts
|

Evoked and induced oscillatory activity contributes to abnormal auditory sensory gating in schizophrenia

Abstract: The ratio of magnetoencephalogram-recorded brain responses occurring 50ms after paired clicks (S2-evoked M50/S1-evoked M50) serves as a measure of sensory gating. An abnormally large ratio is commonly found in schizophrenia. Whether this abnormality indicates impaired gating is debated. Using event-related oscillations the present study sought to elucidate processes contributing to the phenomenon of altered M50 gating ratio. Schizophrenia inpatients (n=50) showed the expected large M50 gating ratio relative to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

7
31
0

Year Published

2012
2012
2020
2020

Publication Types

Select...
5
3

Relationship

2
6

Authors

Journals

citations
Cited by 37 publications
(38 citation statements)
references
References 42 publications
7
31
0
Order By: Relevance
“…In the SZ group 3 patients were left-handed, and 3 were ambidextrous, as assessed by the German version of the Edinburgh Handedness Questionnaire (Oldfield, 1971). The samples partly overlapped with those reported in (Popov et al, 2011;Popov et al, 2013;Popova et al, 2014) assessed during auditory and visual tasks, but there is no overlap in the MEG analyzed for the present report.…”
Section: Participantssupporting
confidence: 54%
“…In the SZ group 3 patients were left-handed, and 3 were ambidextrous, as assessed by the German version of the Edinburgh Handedness Questionnaire (Oldfield, 1971). The samples partly overlapped with those reported in (Popov et al, 2011;Popov et al, 2013;Popova et al, 2014) assessed during auditory and visual tasks, but there is no overlap in the MEG analyzed for the present report.…”
Section: Participantssupporting
confidence: 54%
“…A consistent finding in the schizophrenia literature is a significant decrease in patients’ alpha ERD [47], [50], [51]. One interpretation is that ERD reductions reflect impairments in sensory gating and/or task-related inhibitory mechanisms, which are driven by reductions in post-stimulus alpha activity relative to the pre-stimulus period.…”
Section: Discussionmentioning
confidence: 67%
“…The fact that this relationship survived the band-stop filtering procedure invites the proposition that background alpha may interact with other frequency bands to bring about enhancements in the P1 component. A possible candidate is oscillatory activity in the gamma-band (>30 Hz) since patients with schizophrenia exhibit severe deficits in both these rhythms (see [51]), but also in their interactive nature [79].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The amplitude ratio (S2-evoked/S1-evoked) serves as a measure of auditory sensory gating, with a high ratio suggesting impaired sensory gating in schizophrenia [13], [14]. Analysis of M50 together with time-locked and non-time-locked oscillatory activity in the paired-click design showed that patients’ larger M50 gating ratio was associated with less non-time-locked fronto-parietal desynchronization in the 10–15 Hz frequency band starting 200 ms before the onset of S2 [15]. Patients also produced smaller alpha (8–12 Hz) and gamma (60–80 Hz) responses to the first stimulus.…”
Section: Introductionmentioning
confidence: 99%